Productivity and profitability of rice hybrids at different nutrient management levels under semi-arid conditions of North Eastern Plains Zone - Raj, Rishi Raj; Yadav, M.P.; Kumar, Vikash (Annals of Agricultural Research, 2016)
The research work was undertaken at Student's Instructional Farm, Chandra Sekhar Azad Universityof Agriculture and Technology, Kanpur, India, with the objective of identifying most suitable ricehybrid in terms of yield and economics, and work out the optimum nutrient management level fordifferent rice hybrids. The experiment comprised 12 treatment combinations of 3 nutrientmanagement levels viz. Farmer's dose (80:30:30 N, P2(RDF) (150:75:60:25 N, P2O, ZnSO4kg/ha) and 4 rice hybrids namely, PHB 71, Pro-agro 6444, PAC 832 and Shri RamK2Sonali. The experiment was conducted under split plot design with four replications. Hybrid PHB71 produced significantly higher number of effective tillers, panicle length and grains per panicle ascompared to Pro-agro 6444, PAC 832 and Shri Ram Sonali. The number of effective tillers, paniclelength and grains per panicle increased significantly with increasing levels of nutrient managementand maximised at 125% of RDF. Hybrid PHB 71 produced 6.5 t/ha grain yield which was computedto 8.4, 13.8 and 29.1% higher than the grain yield obtained from PAC 832, Pro-agro 6444 and ShriRam Sonali, respectively. At 125 % of RDF the highest of 6.7 t/ha grain yield of rice was producedand recorded by 9.5 and 49.4% higher than the RDF and farmers dose, respectively. Gross return,net return and benefit: cost ratio were computed maximum in PHB 71 followed by PAC 832, Pro-agro 6444 and Shri Ram Sonali. At the same time gross return, net return and benefit: cost ratio werealso obtained maximum at 125% of RDF as compared to RDF and farmers dose., K2O, ZnSO4O5, K2O5kg/ha) and 125% of RDF (187.5:93.75:75:31.25 N, P2O kg/ha), Recommended dose of fertilisers